EVALUATION OF ZONING SYSTEM POLICY ON THE ADMISSION OF NEW STUDENTS AT THE STATE HIGH SCHOOL LEVEL OF BALIKPAPAN CITY: Evaluasi Kebijakan Sistem Zonasi Pada Penerimaan Peserta Didik Baru Tingkat Sma Negeri Kota Balikpapan - Adji Puteri Mila Maharani; Friska Prastya Harlis (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The zoning pathway is one of the registration pathways in the context of PPDB. This zoning policy demonstrates the government's commitment to ensure that all citizens have access to quality education at the national level. This policy was enacted to break the stigma between schools that are considered favorites and non-favorites. In this case, East Kalimantan Province has implemented a zoning system on PPDB at the high school level, especially in the city of Balikpapan.The purpose of this study is to evaluate the zoning system policy on the admission of new students at the State High School level in Balikpapan City. The research method used is qualitative descriptive with a literature review approach where the primary source is obtained from previous journals and supported by interviews with related sources. The results of this study state that the implementation of the zoning system at the State High School Level PPDB can be said to be quite effective, but with the limitations of State High Schools in the city of Balikpapan, it is a challenge for the government in terms of providing school infrastructure in each sub-district